RAW WATER MANAGEMENT AND PROTECTION EFFORTS IN DRINKING WATER SUPPLY - Yung Savitri; Mochamad Azwar (International Journal of Applied Science and Sustainable Development (IJASSD), 2023)
Scarcity of clean water is one of the main problems in several regions in Indonesia. One of the causes of water scarcity is the availability of raw water sources that are less fulfilling human needs. Raw water with quality, quantity, continuity and affordability are needed as population growth continues to increase. In some areas experiencing water crises, water shortages have occurred almost every year. Thus, the availability of sources of raw water is very important in providing clean water for the community. Selection of the source of raw water for drinking must be qualified in terms of quantity, quality, continuity and affordability (accessibility). Raw water management tailored to the type of raw water used. Raw water sampling conducted using raw water unit building, namely intake, broundcaptering, wells and rainwater. Protection of raw water sources to do with the division of water protection zones that are based with the health and biological factors. Preparation of Raw Water Master Plan has also become one of the solutions for the protection of raw water and mapping potential sources of raw water.